2020
DOI: 10.1080/87559129.2020.1734609
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Anti-diabetic and Cardioprotective Potential of Gallic Acid: A Widespread Dietary Phytoconstituent

Abstract: Gallic acid (GA) is a bioactive phytoconstituent that has been reported to prevent a number of diseases. However, there is no systematic review to-date on its anti-diabetic and cardioprotective potential including molecular mechanisms for such activities. This review aims to summarize the anti-diabetic and cardioprotective effects of gallic acid and further propose a molecular mechanism of its anti-diabetic effects. Accumulation of associated literature was conducted through the use of databases including Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…propyl gallate, octyl gallate, and lauryl gallate) exhibit numerous properties serving as antioxidants, antimicrobials or anticancer, as well as active agents that reduce cellular oxidative stress. [14][15][16] However, concerning biomedical applications and similar to numerous phytochemicals, harnessing the full potential of GA within the human body stumbles with its low bioavailability and bioactivity which are pivotal for any bioactive molecule to be considered efficient. [17][18][19] To overcome these issues, drug delivery systems (DDSs) as polymeric electrospun fiber mats [20][21][22] , nanoparticles [23][24] or hydrogels [25][26][27][28] have considerably grasped attention as a possible way to improve GA's pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…propyl gallate, octyl gallate, and lauryl gallate) exhibit numerous properties serving as antioxidants, antimicrobials or anticancer, as well as active agents that reduce cellular oxidative stress. [14][15][16] However, concerning biomedical applications and similar to numerous phytochemicals, harnessing the full potential of GA within the human body stumbles with its low bioavailability and bioactivity which are pivotal for any bioactive molecule to be considered efficient. [17][18][19] To overcome these issues, drug delivery systems (DDSs) as polymeric electrospun fiber mats [20][21][22] , nanoparticles [23][24] or hydrogels [25][26][27][28] have considerably grasped attention as a possible way to improve GA's pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It can be extracted under different forms from chestnuts, nuts, sumacs, gallnuts, witch hazels, cloves, tealeaves, and other plants . Moreover, it is particularly accessible via the oak bark transformation industry in the form of hydrolyzable tannins. , GA and its ester derivatives (e.g., propyl gallate, octyl gallate, and lauryl gallate) exhibit numerous properties, serving as antioxidants, antimicrobials, or anticancer agents as well as active agents that reduce cellular oxidative stress. However, concerning its biomedical applications, similar to numerous phytochemicals, harnessing the full potential of GA within the human body is limited due to its low bioavailability and bioactivity, which are pivotal for any bioactive molecule to be considered efficient. To overcome these issues, drug delivery systems (DDSs) such as polymeric electrospun fiber mats, nanoparticles, , and hydrogels have attracted considerable attention as possible methods to improve the pharmacokinetics of GA.…”
Section: Introductionmentioning
confidence: 99%
“…Farther, an antidiabetic activity associated with gallic acid has also been reported by [119], Fachriyah et al (2017) [115] and Variya et al (2020) [171]. The recent reported study revealed that gallic acid may also be used as cardio-tonic in conjunction with anti-oxidant and anticancer effects [172].…”
Section: Gallic Acidmentioning
confidence: 76%
“…It was found that Madhugrit substantially improved the glucose uptake activity of L6 cells as observed by the uptake of fluorescent glucose analog 2-NBDG. The hypoglycemic properties of Madhugrit can be attributed to the presence of gallic acid as one of its major phytoconstituents ( 55 ). Gallic acid in vitro is reported to directly inhibit α-amylase activity in an in vitro model system ( 56 ).…”
Section: Discussionmentioning
confidence: 99%